Increasing the thermal endurance of injection molding parts - Глушкова, Д. Б.; Волчук, В. М.; Hlushkova, Diana; Volchuk, Volodymyr (Харківський національний автомобільно-дорожній університет, 2025)
The use of plasma coatings based on wear-resistant materials opens up wide opportunities for improving the operational properties of parts. Currently, there are many technologies for applying such coatings, among which special attention is paid to chemical vapor deposition and the method of condensation of the material under ion bombardment conditions. For the manufacture of molds intended for pressure casting of copper alloys, 4Kh5MFS and 5KhNM steels were selected in this work. The maximum adhesion activity to the substrate and the effect on increasing the thermal endurance of 4Kh5MFS and 5KhNM steels are achieved at a coating thickness of 2–5 μm, the application time varied from 12 to 30 minutes. The coating was applied to the surface of the steel heated to 500 °C during ion bombardment. As a result of the analysis, the deposition of the α-Ti phase was recorded. At the same time, micro-X-ray spectral analysis did not reveal deep penetration of titanium into the substrate. After ion bombardment, the hardness of the surface layer increases from 480–500 MPa to 1050 MPa. The fractal dimension of the surface of the 4 μm-thick titanium nitride coating applied to 4Kh5MFS steel increased from 1.856 to 1.914 compared to thesurface after heat treatment, and for 5KhNM steel after ion bombardment with titanium this parameter increased from 1.829 to 1.897. This result indicates the relationship between the fractal structure and the physical and mechanical characteristics of the coating.
Підвищення термічної витривалості деталей прес-форм лиття під тиском
Keywords: plasma; fractal; structure; hardness; thermal endurance; mathematical model; плазма; фрактал; структура; твердість; термостійкість; математична модель; 519.21; 10.30977/BUL.2219-5548.2025.108.0.25